2023
DOI: 10.1002/anie.202317346
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Electron Redox Reactivity of Thorium Supported by Redox‐Active Tripodal Frameworks

Fang‐Che Hsueh,
Damien Chen,
Thayalan Rajeshkumar
et al.

Abstract: The high stability of the + IVoxidation state limits thorium redox reactivity. Here we report the synthesis and the redox reactivity of two Th(IV) complexes supported by the arene‐tethered tris(siloxide) tripodal ligands [(KOSiR2Ar)3‐arene)]. The two‐electron reduction of these Th(IV) complexes generates the doubly reduced [KTh((OSi(OtBu)2Ar)3‐arene)(THF)2] (2OtBu) and [K(2.2.2‐cryptand)][Th((OSiPh2Ar)3‐arene)(THF)2](2Ph‐crypt) where the formal oxidation state of Th is +II. Structural and computational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 104 publications
0
7
0
Order By: Relevance
“…19,20,33,34 In addition, very recently, Mazzanti and co-workers showed that thorium(IV) complexes supported by redox-active tripodal frameworks could act as a thorium(II) synthon to enable twoelectron redox reactivity. 40 These all involve reduced arene anions as electron reservoirs. However, while transition-metal arene complexes could undergo reversible C−C couplings under redox conditions, 78,79 no such reactivity has been shown for f-block metal arene complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19,20,33,34 In addition, very recently, Mazzanti and co-workers showed that thorium(IV) complexes supported by redox-active tripodal frameworks could act as a thorium(II) synthon to enable twoelectron redox reactivity. 40 These all involve reduced arene anions as electron reservoirs. However, while transition-metal arene complexes could undergo reversible C−C couplings under redox conditions, 78,79 no such reactivity has been shown for f-block metal arene complexes.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…27,35−40 Notably, all attempts to reduce thorium(IV) arene complexes led to ligand-based reduction with the formation of thorium(IV) complexes of reduced arenes (Figure 1a). 27,36,40 Such reduction reactivity is in contrast to that of uranium(IV) analogues, which usually result in uranium-centered reduction. 27,29,41 The different reactivity between thorium and uranium may be attributed to the facts that thorium(IV) is more difficult to reduce than uranium(IV) 42−44 and genuine thorium(III) and thorium(II) complexes are much rarer compared to their uranium(III) and uranium(II) counterparts.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Progress in the field of thorium redox chemistry has lagged behind that of uranium, even though thorium is over three times more abundant than uranium . In fact, most of the literature on thorium chemistry involves its most stable +4 oxidation state. Although there are many studies showcasing the redox chemistry of thorium complexes, many of these require the use of redox-active ligands or reduced arenes. To date, only 12 structurally characterized Th­(III) complexes have been reported. There are also only six published Th­(II) crystal structures, five of which contain the {[C 5 H 3 (SiMe 3 ) 2 ] 3 Th II } 1– anion and one containing the [(C 5 H 4 Si i Pr 3 ) 3 Th II ] 1– anion. As a result, the development of synthetic routes to new examples of Th­(III) and Th­(II) complexes is an important research goal.…”
Section: Introductionmentioning
confidence: 99%
“…These virtues derive from the synergy between the ancillary silanolates and the high-valent molybdenum alkylidyne unit, which has been studied in detail in the past. ,, As a next step, investigating whether these tripodal silanolates also match molybdenum complexes beyond the alkylidyne estate seemed interesting and relevant. Nitrido complexes are obvious candidates, as they are isolobal with the alkylidynes. , As such, they are of interest in their own right and, at the same time, constitute a potential entry point into the realm of low-valent molybdenum silanolate coordination chemistry. , The results of our first foray are summarized below.…”
Section: Introductionmentioning
confidence: 99%